Is the human chin a spandrel? Insights from an evolutionary analysis of ape craniomandibular form - von Cramon-Taubadel, Noreen; Scott, Jill E.; Robinson, Chris A.; Schroeder, Lauren (PLOS ONE, 2026)
Humans are unique among primates in possessing a chin, yet it is currently unclear whether the form of the symphyseal region of the mandible where the chin is located is the product of direct selection or a by-product of evolutionary pressures on other craniomandibular features. Here, we conduct an evolutionary analysis of hominoid craniomandibular traits to test three hypotheses: symphyseal mandibular traits evolved (1) neutrally due to genetic drift, (2) under direct selection, and (3) as a by-product (or “spandrel”) of selection on other craniomandibular traits. Evolutionary rates of morphological change, via Lande’s generalized genetic distance, were estimated along each branch of a fully-resolved hominoid phylogeny to reveal patterns of neutral, stabilizing and directional selection. Directional selection was detected along the branch between humans and the last common ancestor of chimpanzees and humans, against a backdrop of pervasive stabilizing selection and neutral evolution in hominoids. Significant directional selection was found on cranial traits reflecting increased basicranial flexion, neurocranial expansion, and reduction in lower facial prognathism, and on mandibular traits that generate a more parabolic-shaped, gracile mandible with a smaller ramus and shallower corpus. In contrast, of the nine mandibular “chin” traits, only three were under significant direct selection, while the other six were either under no selection or indirect selection. Thus, the results are consistent with the hypothesis that the symphyseal morphology that forms the human chin evolved largely as a by-product (i.e., spandrel) of direct selection for reduced anterior dental size and the craniofacial changes correlated with the evolution of bipedalism in hominins, rather than as a specific adaptation.